Utilization pattern of kangaroo mother care after introduction in eight selected neonatal intensive care units in China - Xin Liu; Zhankui Li; Xiaohui Chen; Bei Cao; Shaojie Yue; Changyi Yang; Qiongyu Liu; Chuanzhong Yang; Gengli Zhao; Qi Feng (BMC, 2020)
Abstract Background Kangaroo mother care (KMC) is an evidence-based and cost-effective intervention that could prevent severe complications for preterm babies, however it has not been widely adopted in China. In this study, we aim to investigate the feasibility and parental experience of adopting KMC in a Chinese context by studying the implementation of a KMC program in eight self-selected neonatal intensive care units (NICUs). Methods A cross-sectional study of 135 preterm infants discharged from eight NICUs in April 2018. For infants information was collected on postnatal day and corrected gestational age (GA) at KMC initiation, frequency and duration of KMC provision and whether the infant was receiving respiratory support. A nurse-administered questionnaire on parents' knowledge and experience of KMC provision was administered to parents providing KMC. Results One hundred thirty-five preterm infants received KMC, 21.2% of all preterm infants discharged. 65.2% of those who received KMC were below 32 weeks GA, 60.7% had a birth weight below 1500 g, and 20.7% needed respiratory support at KMC initiation. Average KMC exposure was greater in infants born at GA < 28 weeks that babies born at greater GA. 94.8% of parents that participated in the parental survey indicated that KMC was positively accepted by their family members; 60.4% of the parents claimed that KMC could relieve anxiety, 57.3% claimed it prompted more interactions with medical staff and 69.8% suggested it increased parental confidence in care for their infants. Conclusions After advocacy, training and promotion, intermittent KMC was initiated on more immature and high-risk infants, and well-accepted by parents. We suggest continuing to promote KMC education to parents and enhancing preterm infant health.